Effect of tetravalent bispecific CD19xCD3 recombinant antibody construct and CD28 costimulation on lysis of malignant B cells from patients with chronic lymphocytic leukemia by autologous T cells - Reusch, Uwe; Le Gall, Fabrice; Hensel, Manfred; Moldenhauer, Gerhard; Ho, Anthony Dick; Little, Melvyn; Kipriyanov, Sergey M. (International journal of cancer, 2004)
To develop an effective antitumor immunotherapy for B-lineage non-Hodgkin's lymphoma, we constructed a tetravalent tandem diabody (tanDb) specific for both human CD19 (B-cell marker) and CD3 (T-cell antigen). Here, we report the effective killing of malignant primary B cells from patients with B-cell chronic lymphocytic leukemia (B-CLL) by autologous T cells induced by tanDb at very low E:T ratios. Mononuclear cells from patients with B-CLL were cultured with bispecific antibody fragments in either the presence or absence of monospecific anti-CD28 antibody. Use of tetravalent tanDbs caused almost quantitative elimination of malignant B cells from the blood samples of 19 patients and some cytotoxic activity in 3 of 23 analyzed cases. In contrast, the structurally similar but bivalent diabody and single-chain diabody demonstrated nearly no antitumor activity in an autologous system. tanDb-induced activation and proliferation of T cells occurred only in the presence of CD19+ target cells. Expression of the B7-1 (CD80) and B7-2 (CD86) molecules on the surface of leukemia cells made unnecessary the additional CD28-costimulation of T cells. When only a few tanDb molecules were present, the effect of CD28 costimulation on T-cell activation was more pronounced. Depending on the patient sample, we observed a 10- to 1,000-fold decrease of the half-maximal concentrations of tanDb for cell lysis. Upon CD28 crosslinking by agonistic MAb, specific tumor cell lysis was found at tanDb concentrations as low as 0.5 pM. These data demonstrate that the tetravalent CD19×CD3 tanDb might be a promising tool for the immunotherapy of human B-cell leukemias and lymphomas. © 2004 Wiley-Liss, Inc.